Efetividade do sistema de justiça criminal brasileiro à luz das teorias sociológicas do crime - Pereira, Alessa Sanny Lima (2020)
The issue of the effectiveness of criminal justice in Brazil goes beyond the limits of mere legislative activity, keeping a close causal relationship with the complex political, economic and social system. Ignoring this context, criminal justice can neither be known nor resolved. The evolution of Criminology has already shown that the phenomenon of crime is multifactorial, establishing a correspondence with several causes, especially those of a social nature. Thus, to disregard the already empirically consolidated knowledge about criminal activity, its motivations, and complexities, is also to make innocuous any attempt of law enforcement. It is in this scenario that the present work will aim to demonstrate the importance of the criminological foundation for the elaboration and execution of criminal policies truly capable of understanding the criminal phenomenon and, therefore, acting on its causes, rather than simply on its consequences. The research method used is the literature review, which will analyze several authors of the different disciplines that from the criminal sciences in order to understand the obstacles to the effective application of criminal law in Brazil